The Impact Of Marketing Communications On The Decline Of The De Mata Museum: A Study Of Traditional Wom Vs E-Wom - Helena Yovita Junijanto; Shellyana Junaedi (FAKULTAS DAKWAH UIN SALATIGA, 2024)
The main objective of this study was to investigate the influence of marketing communication on visitors' interpretation of the De Mata Museum Yogyakarta site. In total, 196 individuals, ranging in age from 15 to 40, visited the De Mata Museum in Yogyakarta before the conclusion of the investigation. Data was collected using a purposive sample technique, Google Forms and a 5-point Likert scale. The data analysis was performed using IBM SPSS Statistics version 25, which included examining variance (ANOVA) and multiple linear regression. The findings indicated that electronic word-of-mouth (e-WOM) had a more significant influence on a physical site's perceived quality than conventional WOM. Significantly, the influence of commercial electronic word-of-mouth (e-WOM) exceeded that of personal WOM. Furthermore, the impact of negative word-of-mouth (WOM) metrics was markedly more substantial than that of good WOM, and negative electronic word-of-mouth (e-WOM) had a broader influence than negative WOM.